Embryo-scale epithelial buckling forms a propagating furrow that initiates gastrulation - Julien Fierling; Alphy John; Barthélémy Delorme; Alexandre Torzynski; Guy B. Blanchard; Claire M. Lye; Anna Popkova; Grégoire Malandain; Bénédicte Sanson; Jocelyn Étienne; Philippe Marmottant; Catherine Quilliet; et al. (Nature Communications, 2022)
Drosophila mesoderm invagination begins with the formation of a furrow. Here they show that a long-range mechanism, powered by actomyosin contraction between the embryo polar caps, works like a ‘cheese-cutter wire’ indenting the tissue surface and folding it into a propagating furrow.